Multiparameter controller usage for gas pumping unit control - Лагойда, Андрій Іванович (Technology audit and production reserves, 2014)
Based on the experiment on a centrifugal supercharger Ц-6,3, which is included in anti-surge regulation of gas pumping units it is defined the productivity change of centrifugal supercharger and changes in the degree of increase in gas pressure, from which is derived the transfer function of a centrifugal supercharger of gas compressor unit. The method of parameter determining of regulator setting through such component of Matlab software as Check Step Response Characteristics block is given. The technological process simulation is conducted with PID, PIDD2-, PIDD2D3-, PDD2-, and PDPD controllers based on the determined values in Matlab software and their optimal settings are determined. During research of system using multi controllers it is found that operation speed of system increases in comparing with PID-controller at: PIDD2 controllers to 4,44 %, PIDD2D3 controllers to 22,67 %, PDD2 controllers to 89,33 %, and PDPD controllers to 98,22 %.